2020
DOI: 10.1155/2020/9049614
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid D Alleviates Cerebral Ischemia-Reperfusion Injury by Suppressing the Cytoplasmic Translocation and Release of HMGB1-Triggered NF-κB Activation to Inhibit Inflammatory Response

Abstract: Inflammatory response participates in the overall pathophysiological process of stroke. It is a promising strategy to develop antistroke drugs targeting inflammation. This study is aimed at investigating the therapeutic effect and anti-inflammatory mechanism of salvianolic acid D (SalD) against cerebral ischemia/reperfusion (I/R) injury. A rat middle cerebral artery occlusion/reperfusion (MCAO/R) injury model was established, and an oxygen-glucose deprivation/reoxygenation (OGD/R) injury model was established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 90 publications
(92 reference statements)
2
16
0
Order By: Relevance
“…However, whether the increase in TLR4 protein expression could alleviate the following inflammation injury remains uncertain. Studies showed that NF-κB could be activated by the upstream molecule TLR4, phosphorylated, and transferred to nuclei, resulting in inflammation injury [13]. In the present work, the expression of pNF-κB in the nuclei increased significantly in the HIBD model 7 days after HIBD, indicating that hypoxia-ischemia activated NF-κB.…”
Section: Discussionsupporting
confidence: 59%
“…However, whether the increase in TLR4 protein expression could alleviate the following inflammation injury remains uncertain. Studies showed that NF-κB could be activated by the upstream molecule TLR4, phosphorylated, and transferred to nuclei, resulting in inflammation injury [13]. In the present work, the expression of pNF-κB in the nuclei increased significantly in the HIBD model 7 days after HIBD, indicating that hypoxia-ischemia activated NF-κB.…”
Section: Discussionsupporting
confidence: 59%
“… 29 , 30 It has been shown that TLR4 contributes to I/R-induced inflammatory response. 31 Our data indicated that the expression of TLR4 was increased in SH-SY5Y cells exposed to OGD/R and in brain tissues of rats subjected to I/R injury. In addition, NF-κB is an essential transcription factor that plays an important role in cell growth and inflammation.…”
Section: Discussionmentioning
confidence: 50%
“… 9 , 32 NF-κB exists in cytoplasm as an inactive dimeric form binding to IκB. 31 TLR4/MyD88 signaling can phosphorylate IκB, and then release the active form of NF-κB (NF-κB translocation from the cytoplasm to the nucleus). 33 NF-κB participates in the pathological process of IS, which can be triggered by ROS, and several inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Post-ischemic inflammation, one of the main pathological features in the early stage of cerebral I/R injury, contributes to the release of pro-inflammatory mediators, which exacerbate cerebral infarction [ 39 ]. Studies have reported that TLR4 expressed on microglia and astrocytes plays a crucial role in the generation of pro-inflammatory cytokines in the initial stage of cerebral I/R injury, whereas pharmacological interventions alleviate cerebral infarction by inhibiting TLR4-mediated microglial and astrocytic activation in the ischemic area in the acute phase of transient MCAo [ 40 ]. In the present study, the TTC-stained brain sections revealed that cerebral infarction was predominantly distributed in the right cerebral hemisphere involving the cortex and striatum at 1 day after 90 min of MCAo.…”
Section: Discussionmentioning
confidence: 99%